Formación integral de la secretaria y su aporte en la gestión administrativa del Gobierno Autónomo Descentralizado Municipal del cantón Quinsaloma - Cabezas Baldeón, Mariuxi Katherine (2021)
The work of the executive secretary is very important within a company because through it there is a link between the different sections of the corporate body, for this reason the person aspiring to this position cannot be taken lightly, it needs to have extensive training in various components such as: communication, administration and customer service, among others. The Municipal GAD of the Quinsaloma Canton to whom this research work is directed requires updating the training knowledge of its administrative personnel, and in turn hiring personnel with skills and abilities that contribute, in the development and improvement of the Quinsaloma Canton, in addition it is intended that the contents and competences, with which secretaries develop in their work do not remain in seniority, that is why in this case study we highlight the importance of the integral training of the secretary in Administrative Management for the proper functioning of the Same. Based on my research, I have identified some techniques and skills that the executive secretary applies in the daily performance of the activities she performs, it can be said that she has a fairly efficient academic record in terms of the management of technological resources, is organized, shows punctuality and responsibility in what is entrusted to him, likewise there is organization in the files entrusted to his charge, which he manages. It is all that a company and a manager need to trust the businesses and other resources that depend on it.